KEGIATAN “FESTIVAL ANAK NEGERI” SEBAGAI WADAH PENGEMBANGAN BAKAT SISWA DI TENGAH PANDEMI COVID-19 - Sugeng Santoso; Ivan Hadi Prawira Negara; Ni Kadek Lisa Pratiwi Damayanti; Yayang Ristiana Putri; Octa Rantika Purnomo; Monica Silvyana Gago (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
Online learning during the Covid-19 pandemic raises many problems, one of them is the students struggle to adapt to the new condition and also the teacher doesn't have preparation to develop the students’ talents because of lack facilities and any other obstacles. To overcome this problem, Angkring Sinau Community in collaboration with Aksara Community held a national children’s festival, namely Festival Anak Negeri. This study aims to analyze the design of activity, the types of competition and the impact of this festival in improving elementary students’ talents. This research was designed using a descriptive qualitative method with Miles and Huberman’s analysis technique. That technique has three elements, namely data reduction, data presentation and verification. After doing the research, it was found that; (1) The planning of Festival Anak Negeri started by forming the committee, determining the branches and themes of the competition, determining the targets and judges, determining the technicalities of the competition and disseminating information; (2) The competitions in Festival Anak Negeri consist of coloring competition, poetry reading competition, storytelling competition and math quiz competition; and the last (3) Festival Anak Negeri has succeeded in developing talents of elementary school’s students during Covid-19 pandemic, this is evidenced by the response and quality of the participants. In the future, this kind of festival will be carried out consistently with wider target audiences with additional types of competitions, thus this activity will be more impactful for a lot of people.